Wage-labour and capital : in commemoration of the Marx centenary 1818 - May 5th, - 1918 - Marx, Karl; Engels, Friedrich (London : British Socialist Party, 1918)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: marxisme; lonen